Phenotypic and functional characterization of intrahepatic T lymphocytes during chronic hepatitis C - Leroy, Vincent; Vigan, Ines; Mosnier, Jean-Francois; Dufeu-Duchesne, Tania; Pernollet, Martine; Zarski, Jean-Pierre; Marche, Patrice N.; Jouvin-Marche, Evelyne (Hepatology (Baltimore, Md.), 2003)
The pathogenesis of liver cell injury during chronic hepatitis C (CHC) is poorly understood. The cellular immune response is thought to play a key role in both inhibition of viral replication and liver pathology. However, little is currently known about which lymphocyte populations and which immune effectors contribute to or control liver damage. We investigated a panel of 15 phenotypic and functional markers of intrahepatic T-lymphocyte subsets irrespective of their antigen specificity in 48 hepatitis C virus (HCV)-infected patients and 8 healthy control subjects. Lymphocyte characteristics were evaluated from liver biopsy specimens both at gene expression level by real-time quantitative reverse-transcription polymerase chain reaction (RT-PCR) and by immunochemistry, in relation with the degree of liver injury and with intrahepatic HCV-RNA levels. As compared with controls, we found major changes in T-lymphocyte subsets in HCV-infected patients, with a significant decrease of T-cell antigen receptor (TCR) δ and CD56 gene expression, associated with a concomitant increase of TCRα and CD8β that were correlated with cytotoxic factors, proinflammatory chemokines, and chemokine receptors including peforin, interferon gamma (IFN-γ), tumor necrosis factor α (TNF-α), RANTES, and CXCR3. The gene expression of CD8β, a specific marker for conventional TCRα +CD8 + lymphocytes, was correlated by multivariate analysis with both alanine aminotransferase (ALT) serum levels and histologic activity index. Furthermore, CD8 staining was observed by immunochemistry in the areas of lobular and piecemeal necrosis. In contrast, no lymphocyte marker was correlated with viral load, measured both in serum and in liver. In conclusion, these results strongly suggest key roles for CD8 + T cells as effectors of liver damage during chronic HCV infection and for their inability to control viral replication. (H epatology 2003;38:829-841.)